Green synthesis of (R)-3-TBDMSO glutaric acid methyl monoester using Novozym 435 in non-aqueous media1. Issue 92 (8th October 2015) - Wang, Hongjiang; Li, Zebiao; Yu, Xiaoxia; Chen, Ruidong; Chen, Xiulai; Liu, Liming
<x xml:space="preserve">Abstract</x> Green synthesis of (R)-3-TBDMSO glutaric acid methyl monoester using Novozym 435 in nonaqueous media.